MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA DAN AKTIVITAS GURU PADA MATERI BIOTEKNOLOGI PANGAN KELAS IX MTs MELALUI MODEL PEMBELAJARAN BERBASIS MASALAH - Dwi Kameluh Agustina (Universitas Islam Balitar, 2015)
This study is aimed at seeing improvement of studnets cognitive learning achievement and teacher activities in food biotechnology subject. The study used Classroom Action Research with two cycles and assigned 30 students of the IX grade of MTs Sunan Ampel, Siman Kepung in 2014/2015. Data were colledted using test and observation. The study found that teaching model using problem-based learning improves teachers ’ classroom activities. Cycle I found students activity 62.5% (fair) increasing to 69.7% (good) in cycle II. Learning mastery increased from 52% in cycle I into 85% in cycle II. Students supplied positive responses on the implementation of problem-based learning model in teaching food biotechnology.